MINORITAS MUSLIM DI AUSTRALIA DAN INGGRIS - Kartini, Indriana (Jurnal Penelitian Politik, 2006)
The war against terrorism has become the main topic and spread a ll over the w orld since the bombing o f WTC building in September 11"' 2001. The issue is that rather fighting terrorist as the actor o f terrorism, the war is blured with fighting M oslem people as the most victimized as the actor o f terrorism. Moslems in Australia and United Kingdom, two countries that become close supporter o f USA in the war against terrorism, has suffered o f negative public perception. It is interesting to analyse policy in those two U S ’ close allies. The research that has been conduct compares p o lic y o f Australia and Britain after the bombing. Image o f Moslem community in those countries is shaped by the role o f mass media as the source o f opinion. The war against terrorism has negative effect that it is victimizing Moslem community as the source o f terror.